Physical Education and Physical Activity Promotion: Lifestyle Sports as Meaningful Experiences - Jordan Wintle (MDPI AG, 2022)
The value of embracing a physically active lifestyle has been well documented in recent times. However, despite this knowledge, physical activity levels in many western societies remain worryingly low in both adult and youth populations. Habit formation in youth is a key indicator of engagement in physical activity as an adult; therefore, maximising opportunities to develop motivation in young people is vitally important to increase the likelihood of maintaining physical activity habits as an adult. A key factor for the development of motivation is school-based physical education. This review considers the current landscape of physical education as a vehicle for physical activity promotion, and suggests that a change of approach that moves away from physical education focusing solely on sport techniques is long overdue. A culturally relevant curriculum that includes lifestyle sports, with a focus on mastery and enjoyment through a meaningful experiences approach, is proposed as a viable update to current practice.